Synthesis, Characterization of Some Thiourea Derivatives Based on 4-Methoxybenzoyl Chloride as Antioxidants and Study of Molecular Docking - Oleiwi, Abdullah Qays; Al-Jeilawi, Oday H. R.; Dayl, Sudad A. (Iraqi Journal of Science, 2023)
Ten new thiourea derivatives 1-10 were prepared in this work using a two-step process that involved reacting 4-methoxybenzoyl chloride with KSCN to afford 4-methoxybenzoyl isothiocyanate. This was followed by reaction with various amines (primary amines, secondary amines, and diamines) to give the aforementioned title products 1-10. These products were characterized by FT-IR, 1H NMR and 13C NMR spectroscopy. Using the DPPH scavenging method, the antioxidant activity of thiourea products was investigated, and derivative 8 had the greatest antioxidant activity in comparison to the other derivatives. Moreover, molecular docking for all compounds was studied using Autodock (4.2.6) software and Bacillus pasteurii urease (pdb id: 4ubp) as a target protein. The best inhibitor activity and docking scores are displayed by compound 7, followed by compounds 5 and 6, which highlight the importance of compounds having two thiourea moieties for higher inhibition activity.